Angular Distributions of Molecular Photofragments by Intense Ultrashort Laser Pulses (Journal of Atomic and Molecular Sciences, 2019)
We theoretically study the photofragmentation reaction of the hydrogen molecular ion $H^+_2$ by asingle intense ultrashort laser pulse. Simulation results obtained from numerical solutions of time-dependentSchrödinger equations show that quantum interference patterns are constructed in the photofragmentspectra and the induced angular distributions of photofragments are sensitive to the wavelength of the laserpulse. These phenomena are successfully explained by using the concept of the light-induced conicalintersection.